Pengelolaan Alih Daya Tenaga Kerja pada PT Pegadaian: Studi Kasus PT Era Permata Sejahtera Kantor Wilayah Bandung - Diaz, Vernanda Oktaviano; Yudhanegara, Firman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Outsourced workforce management plays a crucial role in supporting the operations of financial services companies, including PT Pegadaian (Persero). PT Era Permata Sejahtera is a staffing agency that partners with PT Pegadaian to provide employees for cashier and Customer Relationship Officer (CRO) positions at branches throughout West Java. This study aims to describe the implementation of outsourcing mangement at PT Era Permata Sejahtera, covering employee data administration, payroll management based on the West Java Regency/City Minimum Wage (UMK), operational document administration, and frontline role orientation for workers to be assigned to Pegadaian branches. The method used was descriptive qualitative research through participatory observation during a Field Word Practice (PKL) from December 2025 to February 2026 at the Bandung Regional Office. The research findings indicate that outsourcing management at PT Era Permata Sejahtera has utilized simple digital technologies such as Google Forms, but is not yet supported by an integrated Human Resource Information System (HRIS). Adjusting payroll to account for variations in the regional minimum wage (UMK) across regencies and cities in West Java poses major challenge for the company’s HR administration. This study concludes that the effectiveness of outsourcing management is determined by data accuracy, coordination among units, and compliance with labor regulations, and recommends the adoption for a more integrated HRIS system to improve operational efficiency.